UPAYA PENCEGAHAN DEMAM BERDARAH MELALUI LINTAS PROGRAM BERTERNAK IKAN CUPANG (BETTA SPLENDENS) DI DUSUN MERTOSANAN DESA POTORONO BANTUL - Mohamad Judha (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
The area of Banguntapan Sub-district is a lowland area with a high density, every change of season the incidence of Dengue Fever is quite high, efforts are needed to suppress the development of mosquitoes. One way to break the chain of mosquito breeding is to raise Betta fish, which aims to increase economic income from fish farming. Counseling on fish farming activities in order to prevent mosquito breeding. A total of 23 participants in the Pre-test and Post-test Evaluation of Health Counseling Activities on DHF and its prevention were in the good range. While the results of the evaluation of counseling activities by training participants were in the satisfactory range. Efforts are needed to prevent DHF using simple technology not only to have an impact on reducing incidence and increasing family economy through Betta farming.